Penentuan Lokasi Potensial Sekolah Dasar di Kota Makassar - Nanda Mutiara Zani; Arifuddin Akil; Abdul Rachman Rasyid (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2020)
The availability of educational facilities and an unbalanced number of children iniprimary school age, there are also residental areas that were not covered yet by radius of service coverage. This research aims to 1) Discover the demand of elementary school service based on capacity and range of service; 2) To understand the level of importance of the parameters to determine the location of elementary school; 3) Determine the potential of new elementary school location with zoning system support. The Analytical method used to explore the elementary school sevice was spatial method based on Geographic Information System. Meanwhile the parameter of school location determined by Analytical Hiearcy Process with expert choices. Determining potential school location was done by using grid based analysis by dividing research area into several 50x50 meters grid and rate grid condition. Final accumulative value presented there are 391 potential grids for elementary school in the research area. Potential location were then distributed into 19 sub districts in the research area.